2016
DOI: 10.3390/ma9121012
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiO2-Decorated Boron Particles by Wet Ball Milling and their Photoelectrochemical Hydrogen and Oxygen Evolution Reactions

Abstract: TiO2-coated boron particles were prepared by a wet ball milling method, with the particle size distribution and average particle size being easily controlled by varying the milling operation time. Based on the results from X-ray photoelectron spectroscopy, transmission electron microscopy, energy dispersive X-ray analysis, and Fourier transform infrared spectroscopy, it was confirmed that the initial oxide layer on the boron particles surface was removed by the wet milling process, and that a new B–O–Ti bond w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…However, wet ball milling provides smaller particle size and narrower size distribution [23]. Jung et al [24] found that the size of TiO 2 particles was decreased and showed a uniform size distribution by using a wet ball milling process. Furthermore, phase, crystallite size, and crystallinity of TiO 2 play a critical role for high photocatalytic activity which they can be governed by calcination temperature in the sol-gel method.…”
Section: Introductionmentioning
confidence: 99%
“…However, wet ball milling provides smaller particle size and narrower size distribution [23]. Jung et al [24] found that the size of TiO 2 particles was decreased and showed a uniform size distribution by using a wet ball milling process. Furthermore, phase, crystallite size, and crystallinity of TiO 2 play a critical role for high photocatalytic activity which they can be governed by calcination temperature in the sol-gel method.…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that a mass ratio of 3:7 (R to A) is the best for achieving high photocatalytic activities [ 31 ]. However, other reports detail that even a lesser proportion of R can also yield improved photoactivities, and the parameters like crystallite size, surface area, and optical absorption will determine the PCA in such cases [ 18 ]. Also, a mixture of A and brookite (B), as well as R and B, can result in fast photodegradation rates of organic molecules [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…One must note that the smaller particle size of TiO 2 can result in larger surface area and higher photocatalytic activity. Towards this direction, the grinding process of the powder, like dry/wet ball milling (BM), was employed to obtain smaller particle size and narrower size distribution [ 18 , 19 ]. On the other hand, it is to be noted that phase, crystallite size, and crystallinity of TiO 2 play an important role in the enhancement of photocatalytic activity, and these modifications were attempted by the calcination process.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting application of the wet ball-milling process was reported the same year by Jung et al [126] for the TiO 2 nano-coating of boron particles. Briefly, a tungsten carbide milling jar was filled with titanium(IV) isopropoxide, boron powder (average particles’ size ~ 800 nm), and hexane inside a glove box filled with nitrogen.…”
Section: Part Bmentioning
confidence: 99%
“…The ball-milling-derived TiO 2 -coated nanoparticles were promising for hydrogen and oxygen evolution reactions (HERs, OERs) in photoelectrochemical applications.
Fig. 19TEM image ( a ) and EDX maps ( b – d ) of TiO 2 -coated boron particles wet-milled for 8 h.Reprinted with permission from [126]. Copyright (2016) MDPI
…”
Section: Part Bmentioning
confidence: 99%